1975
DOI: 10.1055/s-0038-1651449
|View full text |Cite
|
Sign up to set email alerts
|

Hyperaggregability of Platelets in Thromboembolic Disorders

Abstract: SummaryPlatelet aggregability was measured using platelet rich plasma (PRP) collected from 197 clinical cases including 52 healthy volunteers. In 31 patients of acute stage of thrombosis (within 2 weeks from the onset), a significant enhancement of platelet aggregation measured 5 min after an addition of 3 and 10 μM ADP or 0.1 and 1 μg/ml of adrenaline to PRP (p < 0.05, compared to the healthy group). Also a significant enhancement of secondary aggregation induced by adrenaline was observed (p <0.05). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1977
1977
2008
2008

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Tests of platelet activation were not performed. Transient platelet hyperaggregability occurs [34]. Acute hemorrhage may cause reactive thrombocytosis, but this was not the cause in any of our patients.…”
Section: Discussionmentioning
confidence: 56%
“…Tests of platelet activation were not performed. Transient platelet hyperaggregability occurs [34]. Acute hemorrhage may cause reactive thrombocytosis, but this was not the cause in any of our patients.…”
Section: Discussionmentioning
confidence: 56%
“…It has been reported that circulating platelet aggregates occur more frequently in patients with transmural myocardial infarction than in patients with subendocardial infarction; 108 ' 274 this is somewhat unexpected because the former condition is more frequently associated with coronary artery thrombosis, and it has been suggested that subendocardial infarction might be asso- 227 Goldenfarbetal. 103 Sano et al 270 Steele et al 304 Salky and Dugdale 267 Frishman et al 97 Yamazaki et al 346 Gormsen et al 104 Zahavi 348 Knudsen et al 162 No 342 Gjesdal 102 Guyton and Willerson 108 Rohrer et al 257 Lowe et al 176 Schwartz et al 274 Amodeo et al 4 Salem et al 264 No ciated with occlusion of the distal coronary vasculature with platelets or platelet-fibrin microthrombi.…”
Section: Referencementioning
confidence: 99%
“…Platelet aggregation curves induced by ADP, adrenaline and collagen were recorded by a platelet aggregation meter (Model DP 247E, Sienco Co., Morrison, Colo., USA). The precise method applied and parameters measured in the aggregation curves have been described in detail previously (Yamazaki et al 1975). A line was tangentially drawn at the steepest part of tracing which occured immediately after the addition of reagents.…”
Section: Methodsmentioning
confidence: 99%
“…The ratio of bp, bs, and b5 to the deflection of platelet free plasma was taken and expressed in percentages. The rate of appearance of bs in the aggregation curves induced by ADP or adrenaline was also counted (Yamazaki et al 1975). Lag time was also measured in collageninduced aggregation curve.…”
Section: Methodsmentioning
confidence: 99%